The Effect of Using Bamboozle on Students’ Speaking Skills in Thailand’s EFL Classroom - Yuliyanto, Slamet; Sukmaningrum, Rahmawati; Adi, A. B. Prabowo Kusumo; Waewchimplee, Waewalee (Universitas Pendidikan Mandalika, 2025)
Improving students’ speaking skills is essential in English language learning, yet many students continue to struggle with vocabulary, pronunciation, and confidence in speaking. This study aims to investigate the effectiveness of Bamboozle, a game-based digital learning platform, in enhancing the speaking skills of third-grade students at Suranaree Wittaya School, Thailand, during the 2022/2023 academic year. Employing a quantitative pre-experimental design, the study involved 29 students who were assessed using a pre-test and post-test. The speaking performance was measured based on a rubric covering segmental and suprasegmental aspects. The results showed a significant increase in students’ speaking scores, with the mean score rising from 55.93 to 79.76. The Wilcoxon Signed Rank Test confirmed the statistical significance of the improvement (p = 0.000). Beyond statistical significance, the results highlight the pedagogical value of integrating game-based digital tools into EFL instruction. Bamboozle’s interactive features such as competitive gameplay, visually engaging design, and real-time teacher feedback proved effective in stimulating motivation, encouraging participation, and reinforcing pronunciation practice. These outcomes suggest that Bamboozle can serve not only as a supplementary activity but also as a structured component of communicative language teaching. The study further implies that similar digital platforms hold potential for improving speaking accuracy and fluency in diverse EFL contexts. Accordingly, this research contributes to the growing evidence that game-based learning can bridge the gap between student engagement and measurable learning outcomes in language education.